Features of clinical manifestations and therapy of human papillomavirus-associated diseases of anogenital localization - Maria V Kail-Goryachkina; Tatiana A Belousova (IP Berlin A.V., 2019)
Relevance. The article deals with one of the most common manifestations of human papillomavirus infection - condylomata acuminata/anogenital warts. Aim. To provide current information on human papillomavirus (HPV), its transmission pathways, epidemiology and pathogenesis of HPV-associated diseases of anogenital localization; to describe in detail clinical forms of anogenital warts; to discuss modern methods of anogenital warts treatment, including destructive (physical, chemical), surgical, immunological and combined ones; to show evidence of effectiveness for the use of inosine pranobex, an immunomodulator with antiviral activity, at genital warts of different localization; to present foreign and domestic studies data. Materials and methods. To write this review a search for domestic and foreign publications in Russian and international search systems (PubMed, eLibrary, etc.) for the last 2-15 years was conducted. The review includes articles from peer-reviewed literature. Conclusion. The use of inosine pranobex in combination with destructive methods for a treatment of HPV-associated diseases contributes to more active resolution of the pathological process, reduces a rate of relapses and prevents carcinogenesis due to effective elimination of HPV from lesions. The drug has a good tolerability, minimal side effects, could be used in individual dose and in combinations with other treatment methods that allows to use inosine pranobex for HPV treatment in a wide range of patients.